2007
DOI: 10.1002/clc.3
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Doppler imaging identifies myocardial dysfunction in adults with marfan syndrome

Abstract: SummaryBackground: Successful prevention of aortic complications has lead to improved survival of Marfan syndrome (MFS). With increasing age, however, ventricular arrhythmia and heart failure are emerging as life-threatening manifestations of myocardial dysfunction.Hypothesis: We sought to investigate whether echocardiography with tissue Doppler imaging (TDI) identifies myocardial dysfunction in adults with MFS.Methods: We performed two-dimensional (2-D) and Doppler echocardiography with TDI in 141 individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 29 publications
4
59
0
2
Order By: Relevance
“…For example, a retrospective study of 143 MFS patients identified that the long-term mortality rate associated with aortic repair was 20% and that congestive heart failure was almost as great a risk factor as rupture/dissection of a secondary aneurysm (19% vs. 23%, respectively) (31). Since first described in a 1985 report (9), cardiomyopathy in MFS has been evaluated in several clinical studies totaling over 800 patients and collectively suggesting an average disease prevalence of approximately 20% with cohort-specific ranges from 0% to 68% (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Different factors are likely to have contributed to this extreme variance; among others, they include the exclusion criteria used in the studies, the size and age of the cohorts examined, the medication status of individual patients, the parameters used to normalize cardiac measurements, and the accuracy and resolution across different imaging modalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a retrospective study of 143 MFS patients identified that the long-term mortality rate associated with aortic repair was 20% and that congestive heart failure was almost as great a risk factor as rupture/dissection of a secondary aneurysm (19% vs. 23%, respectively) (31). Since first described in a 1985 report (9), cardiomyopathy in MFS has been evaluated in several clinical studies totaling over 800 patients and collectively suggesting an average disease prevalence of approximately 20% with cohort-specific ranges from 0% to 68% (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Different factors are likely to have contributed to this extreme variance; among others, they include the exclusion criteria used in the studies, the size and age of the cohorts examined, the medication status of individual patients, the parameters used to normalize cardiac measurements, and the accuracy and resolution across different imaging modalities.…”
Section: Discussionmentioning
confidence: 99%
“…While the prevailing view is that thoracic aortic aneurysm (TAA) and cardiac valve abnormalities overload the left ventricle (LV) by respectively stiffening the aortic wall and increasing valve regurgitation (6), several clinical studies of relatively small cohorts of MFS patients have reported LV pathology in the absence of severe valve regurgitation or aortic surgery, or that is out of proportion with aneurysm growth (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). These findings have been used to argue that mutations in fibrillin 1 may cause ventricular dysfunction by altering the structural properties of myocardial tissue and/ or the local bioavailability of TGF-β signals (6,18).…”
Section: Introductionmentioning
confidence: 99%
“…3,10 Forty years ago, average life expectancy in Marfan syndrome was reduced by approximately one third. 11 In those days before effective surgical approaches to proximal ascending aortic disease, up to 90% of deaths in Marfan syndrome were due to acute aortic dissection or chronic aortic regurgitation.…”
Section: Cardiovascular Features Of Marfan Syndromementioning
confidence: 99%
“…In addition, it is well known that aortic regurgitation could affect left ventricular myocardial segments and global function to some extent. In the study by Rybczynski et al, 1 however, the degree of aortic regurgitation was not well described. Were there any relations of reduced systolic and early diastolic tissue Doppler velocities in adults with Marfan syndrome to the degree of aortic regurgitation?…”
mentioning
confidence: 93%
“…In the study by Rybczynski et al, 1 the authors thought that mutations in Marfan syndrome affect proteins of the myocardial cytoskeleton and extracellular matrix, whereas mutations in familial hypertrophic cardiomyopathy involve different sarcomeric proteins, and that reduced systolic and early diastolic tissue Doppler velocities in adults with Marfan syndrome could be caused by a primary myocardial disease. However, the hypothesis of a primary myocardial disease is not convincing enough because reduced systolic and early diastolic tissue Doppler velocities in adults with Marfan syndrome could be affected by the above-mentioned factors that were not well described.…”
mentioning
confidence: 99%